High body mass index and allergies in schoolchildren: the French six cities study. Issue 1 (24th December 2014) - Saadeh, Danielle; Salameh, Pascale; Caillaud, Denis; Charpin, Denis; de Blay, Frédéric; Kopferschmitt, Christine; Lavaud, François; Annesi-Maesano, Isabella; Baldi, Isabelle; Raherison, Chantal
Abstract : Background: The prevalence of allergic diseases such as asthma, allergic rhinitis and atopic dermatitis is increasing rapidly worldwide, especially among children and in western countries. This coincides with an increase in body mass index (BMI), which might be a major risk factor for atopic diseases. Objectives: To study the relationship between high BMI and allergic diseases, as well as skin-prick test (SPT) positivity and exercise-induced asthma (EIA) in 6733 randomly selected schoolchildren aged 9–11 years in the French Six Cities Study. Methods: A cross-sectional study was carried out in Bordeaux, Clermont-Ferrand, Créteil, Marseille, Reims and Strasbourg. Parental questionnaires based on the International Study on Asthma and Allergies in Childhood (ISAAC) were used to collect information on allergic diseases and potential risk factors. Skin-prick testing to common allergens was performed to identify the existence of an allergic hypersensitivity and an exercise test was also performed to assess EIA. Height and weight were collected by trained investigators. After computing the BMI (weight/height squared), the International Obesity Task Force (IOTF) cut-offs were used to define overweight and obesity. The children were also classified as wheezing or non-wheezing. Results: After adjustment for confounding factors, lifetime asthma was associated with high BMI among non-wheezing children (adjusted OR, aOR=1.98, 95% CI (1.06 to 3.70)). In addition, lifetime and past-year allergic rhinitis was associated with high BMI in wheezing children (aOR=1.63, (1.09 to 2.45) and aOR=2.20, (1.13 to 4.27)). However, high BMI was not significantly associated with eczema, SPT positivity or EIA. Conclusions: This study shows a positive association between high BMI and lifetime asthma in non-wheezing children. High BMI was also associated with lifetime and past-year allergic rhinitis. Further studies are needed to provide causal evidence.